Jumonji domain-containing protein 3 regulates the early inflammatory response epigenetically in human periodontal ligament cells. (September 2018) - Wang, Puyu; Yue, Junli; Xu, Weizhe; Chen, Xi; Yi, Xiaowei; Ye, Ling; Zhang, Lan; Huang, Dingming
Highlights: Jmjd3 is involved in the inflammatory process of HPDLs. Jmjd3 up-regulate the expression of IL-6, IL-8 and IL-12 in HPDLs inflammation. Jmjd3 recruit to the promoter of IL-6 and IL-12 and activate their transcription. Jmjd3 up-regulates IL-6 and IL-12 in an H3K27 demethylation-dependent manner. Abstract: Objective: To investigate the role of the histone 3 lysine 27 trimethylation (H3K27me3) demethylase Jumonji domain-containing protein 3 (Jmjd3) in the epigenetic regulation of the inflammatory response in human periodontal ligament cells (HPDLs). Design: HPDLs were stimulated with lipopolysaccharide from E. coli . The expression of Jmjd3 in HPDLs was examined by quantitative real-time polymerase chain reaction (Q-PCR), Western Blot and immunofluorescent staining. Potential target genes were selected by silencing Jmjd3 and were confirmed by Chromatin Immunoprecipitation (ChIP). Results: Q-PCR, Western Blot and immunofluorescent staining revealed that the expression of Jmjd3 was increased in inflamed HPDLs. Knockdown of Jmjd3 led to the suppression of inflammation-induced up-regulation of interleukin-6 and interleukin-12. Moreover, ChIP assays demonstrated that Jmjd3 was recruited to the promoters of interleukin-6 and interleukin-12b and this recruitment was associated with decreased levels of trimethylated histone 3 lysine 27 (H3K27). Conclusions: It was concluded that Jmjd3 regulated the activation of interleukin-6 and interleukin-12b in the early inflammatory response of HPDLs via demethylation of H3K27me3 at promoters. This molecular event may play an important role in the regulation of the inflammatory response in HPDLs.